Ameliorating effects and autonomic mechanisms of needle‐less transcutaneous electrical stimulation at ST36 on stress‐induced impairment in gastric slow waves. Issue 11 (November 2015) - Zhang, Nina; Song, Gengqing; Chen, Jianfeng; Xu, Feng; Yin, Jieyun; Wu, Qiong; Lin, Lin; Chen, Jiande DZ
Abstract Background and Aim Stress has long been documented to alter gastrointestinal motility. The effects of electroacupuncture (EA) on stress and gastric motility are relatively well known; however, whether EA has an ameliorating effect on stress‐induced dysmotility remained unclear. This study aims to investigate the effects and mechanisms of needle‐less transcutaneous electroacupuncture (TEA) on stress‐induced impairment in gastric slow waves. Methods A watch‐size digital stimulator was developed. Ten healthy volunteers were involved in a four‐session study (control, cold stress, TEA, and sham TEA). Electrogastrograpy was used to assess gastric slow waves, and electrocardiogram was recorded for the assessment of autonomic functions. The recordings were made in each session with/without stress and with TEA at ST36 or sham points. Results The results are as follows: (i) Cold stress‐induced gastric dysrhythmia and impaired normal slow waves (P < 0.01). TEA showed a preventive effect on cold stress‐induced impairment in gastric slow waves. TEA at ST36, but not sham TEA, normalized slow waves (P = 0.03 vs stress; P = 0.44 vs control), attributed to the suppression of gastric dysrhythmia; (ii) Postprandially, there was a decrease in vagal activity in both control (P = 0.004) and stress (P = 0.002) sessions; this decrease was prevented with TEA (P < 0.05). Similarly, there was a postprandial increase in sympathetic activity in both control (P = 0.01) and stress (P = 0.002) sessions, and this increase was suppressed with TEA. Conclusions Needle‐less TEA at ST36 using a watch‐size stimulator is able to improve stress‐induced impairment in gastric slow waves, possibly mediated via the autonomic mechanism. Home‐based needle‐less TEA may be a viable therapy for stress‐induced impairment in gastric motility functions.